Microbiome-Metabolomic Analysis Reveals Beneficial Effects of Dietary Kelp Resistant Starch on Intestinal Functions of Hybrid Snakeheads (Channa maculata ♀ × Channa argus ♂) - Shaodan Wang; Zhiheng Zuo; Bin Ye; Li Zhang; Yanbo Cheng; Shaolin Xie; Jixing Zou; Guohuan Xu (MDPI AG, 2023)
The benefits of resistant starch on hypoglycemia, obesity prevention, antioxidant status and the alleviation of metabolic syndrome have received considerable attention. In this study, we explored how dietary kelp resistant starch (KRS) enhances intestinal morphology and function through a microbiome-metabolomic analysis. Hybrid snakeheads (initial weight: 11.4 ± 0.15 g) were fed experimental diets for 60 days. Fish were fed a basic wheat starch diet and the KRS diet. Dietary KRS improved intestinal morphology and enhanced intestinal antioxidant and digestive capabilities, as evidenced by decreased intestinal damage and upregulated intestinal biochemical markers. The microbiome analysis showed that KRS administration elevated the proportion of butyrate-producing bacteria and the abundance of beneficial bacteria that increases insulin sensitivity. Furthermore, significant alterations in metabolic profiles were observed to mainly associate with the amino acid metabolism (particularly arginine production), the metabolism of cofactors and vitamins, fat metabolism, glutathione metabolism, and the biosynthesis of other secondary metabolites. Additionally, alterations in intestinal microbiota composition were significantly associated with metabolites. Collectively, changes in intestinal microbiota and metabolite profiles produced by the replacement of common starch with dietary KRS appears to play an important role in the development of intestinal metabolism, thus leading to improved intestinal function and homeostasis.